2008
DOI: 10.1128/mcb.01158-07
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Uncouples Hormone-Dependent Chromatin Remodeling from Transcription Complex Assembly

Abstract: Sirtuins, homologs of the yeast SIR2 family, are protein deacetylases that require nicotinamide adenosine dinucleotide as cofactor. To determine whether the sirtuin family of deacetylases is involved in progesterone receptor (PR)-mediated transcription, the effect of sirtuin inhibitor, nicotinamide (NAM), was monitored in T47D breast cancer cells. NAM suppressed hormone-dependent activation of PR-regulated genes in a dosedependent manner. Surprisingly, NAM-mediated inhibition of PR-mediated transcription occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 68 publications
(110 reference statements)
2
17
0
Order By: Relevance
“…2C). Additionally, SRC-3, recently described to mediate PR activation of MMTV in breast cancer cells (27), was also recruited similarly in WT-and AF2-expressing cells. We also tested recruitment of total and activated (phospho-Ser5) RNA polymerase II in response to progestin.…”
mentioning
confidence: 93%
“…2C). Additionally, SRC-3, recently described to mediate PR activation of MMTV in breast cancer cells (27), was also recruited similarly in WT-and AF2-expressing cells. We also tested recruitment of total and activated (phospho-Ser5) RNA polymerase II in response to progestin.…”
mentioning
confidence: 93%
“…Steroid hormone receptors, such as the estrogen (ER) and androgen receptors (AR), as well as the progesterone (PR), glucocorticoid (GR), and mineralocorticoid receptors (MR) are part of a large nuclear receptor family of eukaryotic transcription factors (Aoyagi and Archer 2008; Mangelsdorf, et al 1995; Tsai and Omalley 1994). Steroid hormone receptors play essential roles in numerous biological processes, such as homeostasis, metabolism, cell growth and development (Chawla, et al 2001; Mangelsdorf et al 1995; Tsai and Omalley 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The functional importance of the p160 family lies in the fact that mice lacking p160 genes are defective in nuclear receptor-mediated developmental processes (8 -10). Several studies have indicated that hormone-induced interactions between NRs and co-activators is mediated through a single or multiple copies of conserved motif LXXLL (where L is leucine, and X can be any amino acid) (11), termed the nuclear receptor interaction box or nuclear receptor signature motif (12)(13)(14)(15)(16)(17). NR boxes and flanking residues are grouped into four classes depending on the amino acid residues present at the Ϫ1 and Ϫ2 positions upstream of the LXXLL motif.…”
mentioning
confidence: 99%
“…NR boxes and flanking residues are grouped into four classes depending on the amino acid residues present at the Ϫ1 and Ϫ2 positions upstream of the LXXLL motif. The first three classes were identified by a phage display approach, and the fourth class was identified following analysis of naturally occurring motifs among co-activators (11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%